Penukaran Delivery Order Online dan E-Container Equipment Interchange Receipt Terhadap Impor Barang Menggunakan Petikemas - Juli Prastyorini; Fahreza Achmad Syaputra (Majalah Ilmiah Bahari Jogja, 2020)
This study aims to describe the handling of imported goods using containers using online delivery orders and electronic container interchange receipt equipment. In research the method used is descriptive method. Data sources used in this study were interviews and direct observations in the field. The results of this study show the process of handling imported goods using original bill of lading exchanged with online delivery orders that still use manual systems at shipping companies and in job orders into electronic container equipment interchange receipts using the application clique-247 for containers out of the port of sandar in order to speed up handling of imported goods using containers for service users and service providers to work practically and quickly. Based on the results of interviews, observations, documentation studies and literature studies in research, it can be concluded that online and electronic delivery orders - container equipment interchange receipts that are carried out by the Sea Cargo Expedition operations can issue containers in the port of ship berth. That is, the conceptual model developed and based on theory is almost completely supported by the facts in the field.